Higher Serum Immunoglobulin G3 Levels May Predict the Development of Multiple Sclerosis in Individuals With Clinically Isolated Syndrome - Trend, Stephanie; Jones, Anderson P.; Cha, Lilian; Byrne, Scott N.; Geldenhuys, Sian; Fabis-Pedrini, Marzena J.; Carroll, William M.; Cole, Judith M.; Booth, David R.; Lucas, Robyn M.; Kermode, Allan G.; French, Martyn A.; et al. (Frontiers in Immunology, 2018)
Clinically isolated syndrome (CIS) is a first episode of neurological symptoms that may precede a diagnosis of multiple sclerosis (MS). Therefore, studying individuals with CIS may lead to breakthroughs in understanding the development and pathogenesis of MS. In this study, serum levels of immunoglobulin (Ig)G, IgA, IgM, and IgG1–4 were measured in 20 people with CIS and compared with those in 10 healthy controls (HC) and 8 people with MS. Serum Ig levels in individuals with CIS were compared with a) the time to their conversion from CIS to MS, b) serum levels of antibodies to Epstein-Barr virus (EBV), c) frequencies of T regulatory (Treg), T follicular regulatory (Tfr) and B cell subsets, and d) Treg/Tfr expression of Helios. Serum IgG, IgM and IgG2 levels were significantly lower in people with CIS than HC, and IgG, IgM and IgG1 levels were significantly lower in people with CIS than MS. After adjusting for age, sex and serum 25(OH) vitamin D3 [25(OH)D] levels, CIS was associated with lower serum levels of IgG and IgG2 compared with HC (p=0.001 and p<0.001, respectively). People with MS had lower IgG2 levels (p<0.001) and IgG2 proportions (%IgG; p=0.007) compared with HC. After adjusting for age, sex and 25(OH)D, these outcomes remained, in addition to lower serum IgA levels (p=0.01) and increased IgG3 levels (p=0.053) in people with MS compared with HC. Furthermore, serum from people with MS had increased proportions of IgG1 and IgG3 (p=0.03 and p=0.02, respectively), decreased proportions of IgG2 (p=0.007), and greater ratios of ‘upstream’ to ‘downstream’ IgG subclasses (p=0.001) compared with HC. Serum IgG3 proportions (%IgG) from people with CIS correlated with the frequency of plasmablasts in peripheral blood (p=0.02). Expression of Helios by Treg and Tfr cell subsets from individuals with CIS correlated with levels of serum IgG2 and IgG4. IgG3 levels and proportions of IgG3 (%IgG) in serum at CIS diagnosis were inversely correlated with the time until conversion to MS (p=0.018 and p<0.001, respectively), suggesting they may be useful prognostic markers of individuals with CIS who rapidly convert to MS.